State‐Dependent Memory in Infants. Issue 2 (19th August 2020) - Seehagen, Sabine; Schneider, Silvia; Sommer, Katharina; La Rocca, Laura; Konrad, Carolin
Abstract : Why do infants remember some things and not others? Human infants frequently cycle through different states such as calm attentiveness, wakeful activity, and crying. Given that cognitive processes do not occur in isolation, such fluctuations in internal state might influence memory processing. In the present experiment, declarative memory in 9‐month‐old infants ( N = 96) was heavily state dependent. Infants exhibited excellent retention of a deferred imitation task after a 15‐min delay if their state at encoding was identical to their state at retrieval (e.g., calm). Infants failed to exhibit retention if their state at encoding was different from their state at retrieval (e.g., calm vs. animated). Infant memory processing depends on internal cues.